THE ACTUALIZATION OF INTEGRATIVE THEMATIC LEARNING IN MADRASAH IBTIDAIYAH (MI) THROUGH ARIAS LEARNING MODEL - Nur Hadi (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2017)
This paper aims to describe how to actualize integrative thematic learning that takes place in Madrasah Ibtidaiyah (MI) where during this time the educator sometimes still confused how to do the step, what strategy should be used, what model should be chosen in doing the learning process. A thing that must be done by educators for integrative thematic learning can be implemented properly one of them is by using ARIAS learning model. The ARIAS learning model is able to make integrative thematic learning work well. Because the learning model ARIAS is a learning system characterized by a systematic learning environment, meaningful and simple, able to provide comfort learners follow the learning activities, able to develop students' reasoning ability, able to acquire and mastery of new material, able to foster self-confidence learners, able to grow interest and attention of learners, able to cultivate a sense of pride and satisfaction of learners in following the learning.